Bibliometric and subject analysis of articles in the ethnobotanical field of Iranian medicinal plants (1999 - 2022) - Hossein Batooli; Zahra Batooli; Somayyeh Nadi-Ravandi (Institue of Medicinal Plants, ACECR, 2023)
Background: Ethnobotanical knowledge studies the indigenous, local and traditional uses of plants by different people and cultures. Objective: Analysis of articles in the field of ethnobotanical characteristics of Iranian medicinal plants from the perspective of local people. Methods: The study is a retrospective bibliometric analysis and science mapping. The articles retrieved from five databases were examined and exteracted characteristics such as the name of the region, the number of species, the family with the highest number of species, the plant organ used, the method of using plants, and the therapeutic uses of medicinal plants. Then VOSviewer was used to draw a scientific map. Results: All 145 articles (325 authors and in 59 journals) are divided into three groups, including investigation of the ethnobotanical characteristics of medicinal plants in different regions, the ethnobotanical characteristics of a family/species, ethnobotanical characteristics of Iranian medicinal plants for the treatment/prevention of a disease/disorder. The keywords ethnobotany, medicinal plants, traditional medicine, and ethnopharmacology are among the most frequent keywords and digestive, cold, diabetes, dental, gynecological, respiratory and skin diseases were among the most frequent diseases reported in the articles. Conclusion: The people of different regions of Iran pay attention to the use of different types of medicinal plants to treat diseases. However, the ethnobotanical characteristics of medicinal plants in many regions of Iran have yet to be investigated. Only original research articles published in journals have been reviewed in this study. It is suggested that conference and systematic review articles be evaluated in future studies.